Reactivation of an embryonic cardiac neural crest transcriptional profile during zebrafish heart regeneration - Rekha M. Dhillon-Richardson; Alexandra K. Haugan; Luke W. Lyons; Joseph K. McKenna; Marianne E. Bronner; Megan L. Martik (Proceedings of the National Academy of Sciences, 2025)
During vertebrate development, the heart primarily arises from mesoderm, with crucial contributions from cardiac neural crest (CdNC) cells that migrate to the heart and form a variety of cardiovascular derivatives. Here, by integrating bulk and single cell RNA-seq with ATAC-seq, we identify a gene regulatory subcircuit specific to migratory cardiac crest cells composed of key transcription factors egr1, sox9a, tfap2a, and ets1. Notably, we show that cells expressing the canonical neural crest gene sox10 are essential for proper cardiac regeneration in adult zebrafish. Furthermore, expression of all transcription factors from the migratory cardiac crest gene subcircuit are reactivated after injury at the wound edge. Together, our results uncover a developmental gene regulatory network that is important for CdNC fate determination, with key factors of the program reexpressed during regeneration.